Deficiency in the collection of standards in signature analysis in Kerala - Sandheep P. N. and Dinsh J. Narayankar (Indian Journal of Health and Well - being, 2018)
Forensic document examination mainly concentrated on the analysis of disputed handwriting and signatures and comparison of disputed writing with standard writings. The main aim of Comparison of disputed writings is for the identification of consistencies, natural variations, similarities and dissimilarities etc. These all major characteristics are in accordance with the quality and type of standards. In brief the conclusiveness of the result of the examination depends on the quality of the standards. There are mainly two types of standards as requested and collected. The requested standards are writings which have been created under certain controlled circumstances and with the knowledge that these writings are going to be tested but at the same time the collected standards are away from the disguise as at the time of creation of the collected standards, the writer is not aware about the forthcoming examination. In this study we randomly selected cases from different courts in Kerala and examined the percentage of cases which has standards as admitted, requested and both. The percentage and result of the examination has been being discussed below. As of this study we will get an alert for collecting the proper standards and importance of admitted standards on the forensic signature analysis.